The trial of Joan of Arc - Hobbins, Daniel, 1966- (Harvard University Press, 2005)
Translation based on the Latin text of the trial found in the edition of Pierre Champion, Procès de condamnation de Jeanne d'Arc (Paris, 1920). Includes information on accusations against Joan, Saint Catherine, Charles VII, legal procedure, Saint Margaret, Joan's clothing, alleged cursing, escape, fabrications, hair, horse, idolatry, illness, prophecies, relapse, retrial, alleged sorcery, superstition, voices, weapons, wounds, etc.